Base Line Study : Transparency in the Public Construction Sector in Guatemala - Multi-Stakeholder Group (World Bank, Washington, DC, 2013)
This study examined the level of transparency in the public construction sector in Guatemala to create a benchmark for the implementation of the CoST (Construction Sector Transparency) Initiative in the country. It was based on an analysis of the disclosure of 31 indicators of Material Project Information (MPI), as defined by the CoST Initiative. The study showed that disclosure of Material Project Information in Guatemala is supported significantly by the national legal framework. The law mandates online disclosure of almost 87 percent of the MPI required by the CoST Initiative. This is the highest percentage among countries participating in the CoST Initiative to-date. Yet, an analysis of 16 projects selected randomly in seven Procurement Entities (PEs) - four at the central level and three at the local level - revealed that actual information disclosure only amounts, on average, to 38 percent of the MPI required by law. This represents 34 percent of the MPI required by the CoST Initiative. Procurement Entities (PEs) at the central government level disclose on average 40 percent of the MPI required by the law online in the GUATECOMPRAS (Contracting System of the State of Guatemala) system; PEs at the local level disclose 35 percent. In the project cycle, the stages registering the lowest levels of information disclosure were: design (6.29 percent of the MPI required by the law), execution (5.50 percent), supervision (4.13 percent) and post-contract (19.25 percent). Road infrastructure projects under analysis underwent, on average, 17 variation orders, with additional times and price amounting to 123 percent and 103 percent, respectively. Based on the results of the study, the Guatemalan CoST Initiative will collaborate in its pilot phase with selected PEs to facilitate the analysis and disclosure of MPI throughout the project cycle.